2013
DOI: 10.1016/j.jacc.2013.04.081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Overweight and Obesity on Cardiovascular Events in Asymptomatic Aortic Stenosis

Abstract: In patients with initially asymptomatic AS participating in the SEAS study, overweight and obesity did not influence AS progression or rate of AS-related or ischemic CV events but were both associated with increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 37 publications
2
41
0
2
Order By: Relevance
“…There have been contradictive evidence with regards to the obesity paradox in patients with AS [22,23]. Among 1,664 patients with mild-to-moderate AS participating in the SEAS (Simvastatin Ezetimibe in Aortic Stenosis) study, overweight and obesity were both associated with increased mortality [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been contradictive evidence with regards to the obesity paradox in patients with AS [22,23]. Among 1,664 patients with mild-to-moderate AS participating in the SEAS (Simvastatin Ezetimibe in Aortic Stenosis) study, overweight and obesity were both associated with increased mortality [22].…”
Section: Discussionmentioning
confidence: 99%
“…Among 1,664 patients with mild-to-moderate AS participating in the SEAS (Simvastatin Ezetimibe in Aortic Stenosis) study, overweight and obesity were both associated with increased mortality [22]. On the other hand, Rossi et al have recently found that increased BMI is significantly associated with decreased allcause and cardiovascular mortality in 400 patients with severe AS [23].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the present study, the most reliable are abdominal obesity and increased fasting glucose, which is in agreement with the previous studies that found a significant relationship between these risk factors and the aortic valve calcification 21 and the increased cardiovascular morbidity and mortality. 22,23 However, it is not always easy to explain the mutual influence of the metabolic syndrome and aortic stenosis. Namely, Rogge et al 22 recently showed that overweight and obese patients with aortic stenosis, despite the increased prevalence of hypertension and abnormal left ventricular geometry, did not have more progressive aortic stenosis or higher rate of cardiovascular ischemic events, but had worse survival rates in comparison with the normal weight individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, the authors emphasized that waist circumference was not measured in both studies, which restricts eventual comparison with the patients with the metabolic syndrome. 22,24 The main problem is that BMI represents a measure of total adiposity. Namely, using BMI we could not tell the difference between metabolically active visceral fat, which is associated with increased insulin resistance, inflammation, the renin-angiotensin-aldosterone, and sympathetic nervous system activity, 26 and subcutaneous fat that could have a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with both obesity and hyperlipidaemia are at a high risk of cardiovascular diseases (Rogge et al, 2013). The risk of chronic cardiovascular disorders can be minimised by reducing white adipose tissue (WAT) (Arita et al, 1999).…”
Section: Introductionmentioning
confidence: 99%